Dosimetric validation for an automatic brain metastases planning software using single‐isocenter dynamic conformal arcs. (8th September 2016) - Liu, Haisong; Li, Jun; Pappas, Evangelos; Andrews, David; Evans, James; Werner‐Wasik, Maria; Yu, Yan; Dicker, Adam; Shi, Wenyin
Abstract : An automatic brain‐metastases planning (ABMP) software has been installed in our institution. It is dedicated for treating multiple brain metastases with radiosurgery on linear accelerators (linacs) using a single‐setup isocenter with noncoplanar dynamic conformal arcs. This study is to validate the calculated absolute dose and dose distribution of ABMP. Three types of measurements were performed to validate the planning software: 1, dual micro ion chambers were used with an acrylic phantom to measure the absolute dose; 2, a 3D cylindrical phantom with dual diode array was used to evaluate 2D dose distribution and point dose for smaller targets; and 3, a 3D pseudo‐ in vivo patient‐specific phantom filled with polymer gels was used to evaluate the accuracy of 3D dose distribution and radiation delivery. Micro chamber measurement of two targets (volumes of 1.2 cc and 0.9 cc, respectively) showed that the percentage differences of the absolute dose at both targets were less than 1%. Averaged GI passing rate of five different plans measured with the diode array phantom was above 98%, using criteria of 3% dose difference, 1 mm distance to agreement (DTA), and 10% low‐dose threshold. 3D gel phantom measurement results demonstrated a 3D displacement of nine targets of 0.7 ± 0.4 mm (range 0.2 1.1 mm). The averaged two‐dimensional (2D) GI passing rate for several region of interests (ROI) on axial slices that encompass each one of the nine targets was above 98% (5% dose difference, 2 mm DTA, and 10% low‐dose threshold). Measured D 95, the minimum dose that covers 95% of the target volume, of the nine targets was 0.7% less than the calculated D 95 . Three different types of dosimetric verification methods were used and proved the dose calculation of the new automatic brain metastases planning (ABMP) software was clinical acceptable. The 3D pseudo‐ in vivo patient‐specific gel phantom test also served as an end‐to‐end test for validating not only the dose calculation, but the treatment delivery accuracy as well. PACS number(s): 87.53.Lv, 87.55.km, 87.55.Qr